adultcentrism and the children’s classroom: if you want to teach them you must know who they are - eslava, edgar (childhood & philosophy, 2024)
The paper addresses academic adultcentrism from the perspective of the pre-service instruction and practice of philosophy teachers, based on the experience we have gained while leading a Didactic of Philosophy seminar for a Philosophy and Letters academic program where students are engaged in the designing, implementation and evaluation of academic material and class performance for K-12 schools. After giving a brief presentation of the context in which philosophy teaching takes place, and a description of the logic and horizon that set the basis of our seminar, we define and discuss four particular ways in which adultcentrism permeates the preparation and performance of philosophy classes for classrooms with students ranging from 8 to 15 years old: cognitive, epistemic, pedagogical and disciplinary adultcentrism. As well as some of the ways in which, as part of the seminar, the students and the instructor have devised to address and overcome the adultcentrism problems. At the end of the discussion, an auto-critical note is included in order to show the limits of our own practices and base ground, as well as a way to define new necessary approaches and perspectives required to address both the problems we found to be at the bottom of current teaching practices. As well as n our own expectations, methods and ways to deal with those issues with our pre-service young colleagues.